Quality in Russian Industry: the Providing Mechanism - БурнышевК.; ВандышевМ.; ПрямиковаЕ. (Journal of Economic Sociology, 2010)
The motivation for this paper was the research project “Management, labour relations and class formation on the contemporary Russia” (52 enterprises were covered in the different Russian regions). The enterprises of different fields were taken into analysis, they have different forms of organizational structure but with more or less medium size. The information collection was done by case-study method. The main focus of the paper is the practices of the quality provision, management actions taken in certain situations. It was found out that the quality problem is solved differently today on the Russian enterprises. Some companies provide quality control as control on employees functions. Other companies have more sophisticated means (institutionally and technically) to control the quality. At the same time the quality problem does not exist if do not consider this situation within the development framework. This question is not under discussion on the level of tactics and current business. While in soviet time this problem was out of focus due to the deficit character of economy in Russia it is still not under focus but because of main focus to the costs to stay in the same market niche.